(untitled) (Research, Society and Development, 2021)
With the exaggerated increase in pollution resulting from anthropic actions in the aquatic environment, the importance of using biomonitoring to verify toxic, cytotoxic and genotoxic agents is evident. Therefore, this research aimed to analyze the water quality of Balneário Veneza in the urban area of ​​Caxias-MA, through physical-chemical and genotoxic analyses. For the collection of water samples, five points were chosen through the intensification of bathers and points where there is no evidence of bathers. The points were described in P1, P2, P3, P4 and P5, reaching the ends of the Spa. The water samples were taken to the Physical-Chemistry Laboratory of the SAAE (Autonomous Water and Sewage Service) for physical-chemical analyses. Subsequently, genotoxic tests were performed using the Trad-MCN bioassay. Visible sources of anthropogenic pollution were observed along the entire length of the lake, it also showed a high amount of macrophytes, especially in P1, in the other points, in addition to the intensification of bathers, the water in the lake showed an opaque color. In the chemical analysis, hardness and iron were the parameters that did not comply with the maximum value allowed in Ordinance 05/2017 of the Ministry of Health. The genotoxic tests did not show chromosomal alterations in the tetrads, inferring that the spa water does not have genotoxic substances.